Efektivitas Pendidikan Kesehatan Dengan Media Audio Visual Dan Metode Demonstrasi Terhadap Pengetahuan Dan Kemampuan Remaja Putri Dalam Melakukan SADARI Di SMP Taruna Mandiri Tangerang Selatan 2023 - Kharisma Putri Swastika; Irma Herliana; Emi Yuliza (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Breast cancer is a deadly disease and the most common disease in women is breast cancer. Early detection efforts can be carried out through breast self-examination or SADARI, which is a method for early detection in finding breast cancer as early as possible and still at an early stage. The aim of this research is to determine the effectiveness of health education with audiovisual media and demonstration methods on the knowledge and abilities of young women in carrying out SADARI. The type of research used is experimental research with the research design used being pre-experimental with a two group pre-post test design approach. The sampling technique used proportional stratified random sampling and purposive sampling so that a sample of 40 female students was obtained, divided by 20 (Audiovisual), 20 (Demonstration). The data analysis test used the paired t-test statistical test. The research results showed that there were significant changes in scores before and after health education was carried out using audiovisual media and demonstration methods. so that there is an influence of providing health education using audiovisual media on the knowledge and ability of young women to do SADARI (p value 0.000). There is an influence of providing health education using the demonstration method on the knowledge and ability of young women to do SADARI (p value 0.000). The results of the paired t test showed that health education using audiovisual media and demonstration methods was effective on the knowledge and ability to perform SADARI among young women at SMP Taruna Mandiri South Tangerang (p value = 0.000). Based on the research results, it is hoped that teenagers will increase their information and be able to carry out the SADARI application.